2007
DOI: 10.3139/146.101545
|View full text |Cite
|
Sign up to set email alerts
|

Vegard's law: a fundamental relation or an approximation?

Abstract: Vegard's law has been used extensively in mineralogy, metallurgy and materials science for the past six decades. According to the law, unit cell parameters should vary linearly with composition for a continuous substitutional solid solution in which atoms or ions that substitute for each other are randomly distributed. Although the law was postulated on empirical evidence, several cases of both positive and negative deviations from this law have been documented. Its theoretical foundations have not been critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
106
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(122 citation statements)
references
References 5 publications
(2 reference statements)
12
106
0
4
Order By: Relevance
“…This indicates formation of an alloy which is in accordance with Vegard's Law. 16,33 However, as explained before, the introduction of Sn into Pt 64 Sn 15 Ru 13 Ni 8 /C does not elicit any shifts as compared to pure Pt.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This indicates formation of an alloy which is in accordance with Vegard's Law. 16,33 However, as explained before, the introduction of Sn into Pt 64 Sn 15 Ru 13 Ni 8 /C does not elicit any shifts as compared to pure Pt.…”
Section: Resultsmentioning
confidence: 94%
“…This indicates formation of an alloy which is in accordance with Vegard's Law. 16,33 However, as explained before, the introduction of Sn into Pt 64 Sn 15 Ru 13 Ni 8 /C does not elicit any shifts as compared to pure Pt.The crystallite sizes, obtained by means of DebyeScherrer's equation, 27 are in the 7.40-22.50 nm range. The great difference observed among the different reflection planes attest to the high heterogeneity of the particles formed by the DPP method.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…where V M (HfX) is the volume (cm 3 /mol) of each HfX compound; Z B (HfX) is the bonding valence in (el/atom) rationalized from Vegard's law [44]:…”
Section: Elastic Propertiesmentioning
confidence: 99%
“…2.1 is quadratic). A complete study on this can be found in the work done by K.T Jacob, Shubra Raj and L. Rannesh [Jacob 2007]. Most interesting is the controversy on the bowing parameter of InGaN.…”
Section: Crystalline Structure Of Iii-nitridesmentioning
confidence: 94%